(untitled) (International Seven Journal of Multidisciplinary, 2024)
We present the journalism course at the University of Planalto Catarinense (UNIPLAC) with the aim of analyzing the changes that have occurred in the curricular matrix of this course and the implications for the training of telejournalists. In order to understand these transformations, we analyzed the curricular matrices from 2011 to the current one. We provide some background on the history of teaching telejournalism. We also highlight the importance of initial and continuing training for professionals in the field. The curriculum matrix is fundamental, but the theory and practice experienced through the actions of the teachers is what will provide the basis for the journalist’s training.